PERSEPEKTIF BIBLIKAL TENTANG TOLERANSI DAN PERAN ORANG PERCAYA DI ERA GLOBALISASI - Fati Aro Zega; Yonatan Alex Arifianto (Alucio Dei, 2021)
The church or Christians are a component of society that does not live separately from other groups. Moreover, in the current era of globalization, everyone must be able to live together with other groups and people, become members of a community, both in the local environment and in the wider environment. Through a qualitative descriptive method with a literature study approach, the researcher describes the purpose of this paper that life together in a society with various backgrounds and ideals requires a spirit of tolerance. First of all, explaining the meaning and limits of the meaning of tolerance, then finding out Christian tolerant attitudes, through learning from the biblical review of tolerance according to the Bible. So that it underlies believers to have the correct foundation of tolerance based on the Christian faith. Thus, this study seeks to actualize tolerance in the teachings of the Lord Jesus and the Letter of Paul. As an application for today's believers, understanding tolerance means being wise, open to differences and living based on love.